Humanisme dalam Konsep Pendidikan Akhlak Said Nursi - Ihya' Ulumuddin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Discussion of humanism becomes important when humans pitted with problems of life which is too complex to make man -has or will- lose control of human values that led to a tendency to be unhumanistic. For that attitude heed human values proportionally becomes inevitable. And, through moral education, Said Nursi realize universal in human beings through strengthened positive natural forces in man and in turn, strengthen the values of humanism itself. In this study, it can be concluded that the values of humanism in the thought of Said Nursi moral education is manifested in the form of respect for human dignity as the nature and enforcement of social justice in the process of moral education affairs. While in the context of relevance to the moral education Said Nursi, the idea is still very relevant, as reflected in the form of habituation and planting karimahs moral and avoid madhmumahs moral which incidentally be scope for any material moral education at the level of madrasah institutions which was held today.Keywords: Humanism, Education, Morals, Said Nursi.